Os discursos e as ações das equipes gestoras numa rede de ensino confessional e suas implicações na práxis docente - Schmitt, Miguel ângelo (2013)
This study is based on a research which seeks to analyze the practices of school management teams in the schools of a network of confessional teaching, concentrated on the following questioning: Is there consistency between the discourse and the actions of the management teams of the schools of the confessional schools network and in what way do this discourse and these actions implicate in the teaching praxis? For the construction of the research process, we opted for a case study with a qualitative theoretical-methodological focus and the instruments which are being used for collecting the data for the research are: analysis of documents, participant observations, semi-structured questionnaires and interviews. For the analysis of the data we opted to use discourse analysis. The findings of the research show that inconsistencies do exist which generate approximations and distancing between the desires expressed in the documents which guide the educational schools/units of the teaching network researched. These inconsistencies permeate lines much more tenuous than the conscious desire of the manager and most of the time arise without the manager him/her self or the managing teams perceiving that it happened or how it happened. There is a need to rethink not only the role of the management teams and the processes of their formation, but also the processes in which they are inserted and how these processes interfere in the production of the inconsistencies found day to day in management.